The Approaches to Teaching Literature for EFL Young Learners - Fauziah, Fauziah (Yayasan Visi Intan Permata, 2016)
This paper reports on a case study of the teacher’s approaches to teaching literature for young learners in Bandung. The research is an attempt to respond to controversy among the use of literature as a media in teaching English for young learners in Indonesian context. Besides, several English teachers have no idea on how to use poetry as learning material. An English teacher and nine six-grade students were participated in this interpretive qualitative case study. Three research instruments, which were observation, interview, and document, were used. Classroom observation as a primary instrument was triangulated by using interview and document analysis. The results showed that: 1) there were three phases in teaching; initial, exploration, and evaluation phase; 2) under the guideline to choose related topic to nature of young learners, the Language-Based Approach (LBA) was the main used approach, followed by Reader-Response Approach (RRA) and Information-Based Approach (IBA); and 3) The teacher played important roles in building classroom atmosphere.